Politik Uang Pada Pilkada Merangin Tahun 2024 - Salman, Salman; Suparta, Endang; Cantika, Fuji (PT. Meja Ilmiah Publikasi, 2025)
Money politics is the biggest bugbear in every political recruitment, including in regional head elections (pilkada). Through the pilkada, it is expected that qualified regional leaders will be elected according to the will of the people, but in its implementation, one of the